Recently Discovered Bosnian Franciscans’ Manuscripts in Turkish - Čaušević, Ekrem; Andrić, Marta (Prilozi za orijentalnu filologiju, 2017)
Five manuscripts in the Turkish language were recently discovered in the library of St John the Baptist Monastery in Kraljeva Sutjeska (Bosnia and Herzegovina), which V. Boškov does not mention in his 178 Ekrem Čaušević – Marta Andrić Catalogue. Even though the number of these is small, their significance lies in the fact that this scarce corpus of Turkish texts does enrich our current insights on Franciscans, their interest for the Turkish language and peculiarities of the so-called Bosnian Turkish (idiom). In our research of the manuscripts from Kraljeva Sutjeska, we learned the following new insights: 1. according to our findings, the oldest Franciscan Turkish-Latin dictionary until now and the grammar of Turkish language were completed in 1815; 2. the library of the monastery preserves one more grammar by father Mato Mikić Kostrčanec (1826-1862), which he composed on the basis of notes taken during his professor’s lectures; 3. the small Turkish-Latin-Bosnian dictionary by Filip Poljaković is the first found thematic Latin-Turkish-Bosnian dictionary; 4. Bosnian Franciscans composed and/or copied grammars of Turkish during their training in Đakovo (Croatia). Whether they studied Turkish in Đakovo is not known.